Knowledge Sharing pada Sektor Publik: Analisis Systematic Literature Review dengan Vos Viewer - Muchtar, Muhammad; Rofaida, Rofi; Disman, Disman (Journal of Management and Business Review, 2025)
The public sector, as the front guard of public services, has a huge responsibility in ensuring efficiency, effectiveness and innovation in the delivery of public services. One of the keys to achieving this goal is through the practice of Knowledge Sharing, or sharing knowledge, at all levels of the organization. This research aims to delve into the practices of Knowledge Sharing in the public sector as an effort to enhance efficiency and effectiveness in the delivery of public services. However, the limited research investigating Knowledge Sharing practices in the public sector poses a challenge that needs further exploration. The methodology employed in this research involves utilizing data from 165 articles indexed by Google Scholar and Scopus, using the Publish or Perish application. Bibliometric analysis includes visual mapping using Vos Viewer to identify research trends, frequently occurring keywords, and the density of research on various topics. Network visualization illustrates clusters of terms that are the focus of research, such as performance, information exchange, knowledge creation, and motivation. By combining data from network visualization, overlay visualization, and density visualization, this research provides a comprehensive overview of the development of Knowledge Sharing research in the public sector. It identifies that topics such as codification and incentives are still underexplored, presenting opportunities for further research in the future.